Analysis of coliform bacteria contamination in drinking water refill in Ambon City - Nikijuluw, Monica; Pattipeilohy, Mery; Mahulette, Ferymon (BIOEDUPAT: Pattimura Journal of Biology and Learning, 2023)
In recent years, refillable drinking water businesses have grown rapidly in several cities in Indonesia, including Ambon City. On the one hand, Refillable Drinking Water Depots (DAMIU) support efforts to realize a healthy society by expanding the reach of clean water consumption, On the other hand, DAMIU tend to be problematic when faced with business interests. Feces contain coliform bacteria which is an indicator of water contamination. This study aims to determine the presence of coliform bacteria in Ambon City. The samples used in the study came from three sub-districts of refill drinking water depot sources, namely the Teluk Dalam sub-district, Nusaniwe sub-district, and Baguala sub-district. Microbiological testing of refill drinking water using MPN (most probable number) method. The MPN test results showed that three refill drinking water samples were not contaminated with coliform bacteria because there was no turbidity or gas formation in the Durham tube for gas-forming bacteria. This indicates that the three refill drinking water samples tested microbiologically have good quality and are safe for consumption, because in 100 ml of water no coliform bacteria were found in accordance with Permenkes No. 492/Menkes/Per/IX/2010 regulations on the requirements and supervision of water quality, which states that the microbiological requirements for drinking water are MPN Coliform /100 ml sample = 0. There are no coliform bacteria in the refillable drinking water depot in Ambon City so the water is suitable for consumption